Control flujo de potencia del S. N. I. de Ecuador en Base a FACTS y sistemas WAMS - Toctaquiza Vargas, Juan Carlos (2015)
The issue addressed in this thesis is Control power flow of Ecuador SNI based on FACTS and WAMS systems; these efforts are represented in simulations that occur in situations of peak demand and energy falls in the trunk ring. Through WAMS systems innovation arises existing technology by which the mentioned systems will provide to the National Interconnected System reliability. Especially it will let very short time reaction. The systems for the energy power is maintained at normal operating limits and there is required stability. The combination of these two technologies (FACTS and WAMS) means that the grid can reach their maximum operating as confirmed by simulations similar electrical systems in other countries. Therefore, it is concluded that through FACTS and WAMS systems the national grid of Ecuador enhance its scope and may improve performance especially in its backbone ring. In a near future, we can turn into internationally competitive and be a leader in Latin America energy.